THE INFLUENCE OF PRODUCT QUALITY PRICE AND BRAND IMAGE ON PURCHASE DECISION OF BREAD BREAD SARI BREAD (Study on Sari Roti Consumers in Semarang City) - Septytiana Wahyu Mulyadi; Wahyu Hidayat (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
In modern times like this, bread is increasingly unlimited usable substitute for breakfast, for lunch, and even for dinner. Along with the development of times and innovations, there are many white bread products from various brands. In 2018 Sari Roti experienced a significant decrease in sales. To retain consumers, efficient strategies are needed, such as improving product quality, affordable prices, and a good brand image. The purpose of this research was to determine the impact of product quality, price, and the brand image on buying decisions on Sari Roti. The type of this research was explanatory research with the population taken were people who had bought, eaten and made decisions as Sari Roti consumers and took 100 people with a non-probability sampling technique through purposive sampling technique and accidental sampling technique. The method used to collect the data was a questionnaire system. This research used quantitative analysis with validity test, reliability test, correlation coefficient, determination coefficient, simple and multiple regression analysis, and significant test (t-test and f test) with SPSS software version 2.2. The research’s result shown there’s an indication that the quality of food products, price, and brand image influence purchasing decisions. Based on the results, the writer suggested reviewing the designated price by giving discounts to compete with other competitors, improving service and menu innovation on the food product.